VIPOMA: A RARE CAUSE OF CHRONIC DIARRHOEA WITH HYPOKALEMIA, METABOLIC ACIDOSIS AND PANCREATIC MASS - I, Ilham; K, Nor Azmi; K, Waye Hann; C, Ian; Y, Azyani; RH, Lizawati (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Vasoactive intestinal peptide tumour or VIPoma is a rare pancreatic neuroendocrine tumour (PNET) with the incidence of 1 in 10 million population. The characteristic presentation of VIPomas are profuse diarrhoea with hypokalaemia and metabolic acidosis. We report a case of VIPoma who presented to our centre and was thoroughly investigated for his chronic diarrhoea. CASE A 40-year-old gentleman had 7-months history of chronic watery diarrhoea and severe weight loss despite multiple courses of antibiotics. Clinically he was cachexic looking with no other abnormalities on examination. Upon presentation there was hypokalaemia, hypophosphataemia, metabolic acidosis and acute kidney injury. He was thoroughly investigated for infections which were negative, while his endoscopies showed only mild gastritis and colitis. Despite intensive fluid replacements, anti-emetics and antidiarrhoeals his symptoms persisted. CT Abdomen revealed a large pancreatic tail mass with hypodense necrotic centre and calcification. Classical tumour markers for pancreatic adenocarcinoma (CA-19-9 and CEA) were negative. A diagnosis of VIPoma was made based of the clinical features but serum VIP levels were not sent due to patient’s financial constraint. There was also a remarkable response to a trial of somatostatin analogue with symptoms resolving upon administration of octreotide, subcutaneously. Distal pancreatectomy and splenectomy were performed and patient’s gastrointestinal symptoms resolved immediately. Histopathological examination (HPE) confirmed a grade 1 (pT3 N1 Mx) PNET but unfortunately immunohistochemical staining for VIP is not available in our centre. Postoperatively, patient is recovering well and is scheduled for a 68-Ga-DOTATATE PET/CT scan. CONCLUSION This case illustrated a patient diagnosed as VIPoma based on (i) characteristic diarrheagenic symptoms, (ii) typical biochemical features, (iii) radiological evidence of a distal pancreatic mass, (iv) positive response to somatostatin analogue and (v) HPE findings of a NET.